Registration of 'Earl' Hard White Winter Wheat. Issue 3 (25th May 2017) - Carter, A. H.; Kidwell, K. K.; Balow, K. A.; Burke, A.; Shelton, G. B.; Higginbotham, R. W.; DeMacon, V.; Lewien, M. J.; Chen, X. M.; Engle, D. A.; Morris, C. F.
Abstract : End‐use quality and yield potential are the most important traits for hard white winter wheat ( Triticum aestivum L.) cultivars produced in the Pacific Northwest region of the United States. The objective for the development of 'Earl' (Reg. No. CV‐1127, PI 680639) was to provide a hard white winter cultivar that meets end‐use quality expectations and performs well agronomically. Earl was developed and released in September 2014 by the Agricultural Research Center of Washington State University. It was tested under the experimental designations LasWA8061‐75, and WA8184, which were assigned through progressive generations of advancement. Earl is a semidwarf cultivar adapted for the intermediate‐ to high‐rainfall (>400 mm of average annual precipitation), unirrigated wheat production regions of Washington. Earl has high‐temperature, adult‐plant resistance to stripe rust, above‐average grain protein concentration, and high grain volume weight with end‐use quality properties similar to those of hard red winter wheat cultivars 'Bauermeister', 'Finley', and 'Whetstone'.